THE ROLE OF TIMBER IN THE GLOBAL ECONOMY: A SUSTAINABLE PERSPECTIVE - Zara Ali; Roya Zahir; Jamil Khan (Yayasan Adra Karima Hubbi, 2025)
Timber has long been a cornerstone of the global economy, serving as a key raw material in construction, furniture manufacturing, and paper production. However, the growing concerns over deforestation, climate change, and resource depletion have raised questions about the sustainability of timber production and its long-term impact on the environment. Understanding the role of timber in the global economy from a sustainable perspective is crucial for balancing economic development with environmental conservation. This study aims to explore the economic importance of timber in various industries and evaluate its role in sustainable development. It seeks to assess the current trends in timber production and consumption while identifying the challenges and opportunities for promoting sustainable practices in the timber industry. The study employs a mixed-methods approach, combining quantitative data analysis of global timber trade statistics with qualitative case studies of sustainable forestry practices. Data from international trade reports, environmental NGOs, and industry surveys were analyzed to evaluate the economic contribution of timber and its environmental impact. The results reveal that timber remains a vital economic resource, contributing significantly to the global GDP, particularly in developing countries. However, unsustainable logging practices threaten forest ecosystems, which necessitates urgent policy interventions. The study highlights successful examples of sustainable forestry management and certification systems that can mitigate the negative environmental impacts of timber production. The findings suggest that while timber continues to be economically significant, sustainable forestry practices are essential for ensuring the long-term viability of the timber industry. Recommendations include strengthening international regulations, promoting sustainable forestry certification, and investing in forest restoration initiatives.